Blockade of 4-1BB and 4-1BBL Interaction Reduces Obesity-Induced Skeletal Muscle Inflammation. (18th December 2013) - Le, Ngoc Hoan; Kim, Chu-Sook; Tu, Thai Hien; Choi, Hye-Sun; Kim, Byung-Sam; Kawada, Teruo; Goto, Tsuyoshi; Park, Taesun; Yoon Park, Jung Han; Yu, Rina
Abstract : Obesity-induced skeletal muscle inflammation is characterized by increased macrophage infiltration and inflammatory cytokine production. In this study, we investigated whether 4-1BB, a member of the TNF receptor superfamily (TNFRSF9) that provides inflammatory signals, participates in obesity-induced skeletal muscle inflammation. Expression of the 4-1BB gene, accompanied by increased levels of inflammatory cytokines, was markedly upregulated in the skeletal muscle of obese mice fed a high-fat diet, in muscle cells treated with obesity factors, and in cocultured muscle cells/macrophages. In vitro stimulation of 4-1BB with agonistic antibody increased inflammatory cytokine levels in TNFα -pretreated muscle cells, and this effect was absent in cells derived from 4-1BB-deficient mice. Conversely, disruption of the interaction between 4-1BB and its ligand (4-1BBL) with blocking antibody decreased the release of inflammatory cytokines from cocultured muscle cells/macrophages. Moreover, deficiency of 4-1BB markedly reduced macrophage infiltration and inflammatory cytokine production in the skeletal muscle of mice fed a high-fat diet. These findings indicate that 4-1BB mediates the inflammatory responses in obese skeletal muscle by interacting with its ligand 4-1BBL on macrophages. Therefore, 4-1BB and 4-1BBL may be useful targets for prevention of obesity-induced inflammation in skeletal muscle.